Culture Change in Long-Term Care-Post COVID-19: Adapting to a New Reality Using Established Ideas and Systems. Issue 2 (9th June 2023) - Iyamu, Ihoghosa; Plottel, Louis; Snow, M. Elizabeth; Zhang, Wei; Havaei, Farinaz; Puyat, Joseph; Sawatzky, Richard; Salmon, Amy
Abstract: The response to the COVID-19 pandemic in long-term care (LTC) has threatened to undo efforts to transform the culture of care from institutionalized to de-institutionalized models characterized by an orientation towards person- and relationship-centred care. Given the pandemic's persistence, the sustainability of culture-change efforts has come under scrutiny. Drawing on seven culture-change models implemented in Canada, we identify organizational prerequisites, facilitatory mechanisms, and frontline changes relevant to culture change that can strengthen the COVID-19 pandemic response in LTC homes. We contend that a reversal to institutionalized care models to achieve public health goals of limiting COVID-19 and other infectious disease outbreaks is detrimental to LTC residents, their families, and staff. Culture change and infection control need not be antithetical. Both strategies share common goals and approaches that can be integrated as LTC practitioners consider ongoing interventions to improve residents' quality of life, while ensuring the well-being of staff and residents' families.